2005
DOI: 10.1002/cbic.200400260
|View full text |Cite
|
Sign up to set email alerts
|

Forced Intercalation Probes (FIT Probes): Thiazole Orange as a Fluorescent Base in Peptide Nucleic Acids for Homogeneous Single‐Nucleotide‐Polymorphism Detection

Abstract: Fluorescent base analogues in DNA are versatile probes of nucleic acid-nucleic acid and nucleic acid-protein interactions. New peptide nucleic acid (PNA) based probes are described in which the intercalator dye thiazole orange (TO) serves as a base surrogate. The investigation of six TO derivatives revealed that the linker length and the conjugation site decided whether a base surrogate conveys sequence-selective DNA binding and whether fluorescence is increased or decreased upon single-mismatched hybridizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
177
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(182 citation statements)
references
References 85 publications
3
177
0
2
Order By: Relevance
“…[22,38] Previous studies demonstrated the synthesis [39] and useful features, such as high affinity of FIT-PNA to complementary DNA, nondiscriminate pairing of TO to all canonical DNA bases, [38] high specificity for complementary sequences, and enhancement of steady-state fluorescence emission upon formation of matched probetarget complexes with attenuated fluorescence in response to binding to single-nucleobase-mismatched targets. [37,40] One of the intriguing opportunities provided by such base replacement is to localize cyanine dyes to a specific site in the nucleic acid duplex and to assess the optical properties of this isolated binding mode without the problem of competition from other binding sites. Here we provide a detailed analysis of the base-pair dependence of the UV-visible absorbance, steady-state and time-resolved fluorescence-emission properties and compare enforced binding of thiazole orange with the "classical mode" binding of free TO-PRO1.…”
Section: Introductionmentioning
confidence: 99%
“…[22,38] Previous studies demonstrated the synthesis [39] and useful features, such as high affinity of FIT-PNA to complementary DNA, nondiscriminate pairing of TO to all canonical DNA bases, [38] high specificity for complementary sequences, and enhancement of steady-state fluorescence emission upon formation of matched probetarget complexes with attenuated fluorescence in response to binding to single-nucleobase-mismatched targets. [37,40] One of the intriguing opportunities provided by such base replacement is to localize cyanine dyes to a specific site in the nucleic acid duplex and to assess the optical properties of this isolated binding mode without the problem of competition from other binding sites. Here we provide a detailed analysis of the base-pair dependence of the UV-visible absorbance, steady-state and time-resolved fluorescence-emission properties and compare enforced binding of thiazole orange with the "classical mode" binding of free TO-PRO1.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Instead of using interactions between two extrinsic probes, interactions of one fluorophore with DNA bases can be used for specific detection of nucleic acid sequences. [13,14] Besides the use of fluorescein, [15,16] very recently fluorene has also been incorporated into the loop structure of a hairpin architecture. [17] A single base mismatch was detected by de-quenching upon hybridization with the fully matched target and quenching upon hybridization with a target containing a single base mutation.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] YO and TO have also been covalently linked to oligonucleotides and inserted into peptide nucleic acids constructs, which become fluorescent upon hybridisation of the light-up probe to a specific complementary strand. [32][33][34][35][36][37][38] The origin of the very high contrast in emission between the free and the bound form of the dyes has long been thought to be due to an ultrafast decay of the excited state of the free form through a large-amplitude torsional motion around the monomethine bond connecting the benzoxazole, benzothiazole and quinoline moieties, respectively. [39,40] This isomerisation mechanism is blocked upon intercalation of the dyes into DNA and, as a consequence, they light-up by three orders of magnitude.…”
mentioning
confidence: 99%